Factors influencing willingness to participate in multi-stakeholder platform by smallholder farmers in Northern Ghana: Implication for research and development - Edward Martey; Prince M. Etwire; Alexander Nimo Wiredu; Wilson Dogbe (Agricultural and Food Economics, 2014)
Innovation platforms are established to facilitate open communication and collaboration among various actors usually within a value chain to promote collective resource management. The concept of innovation platform as a strategy of entry point for operationalization, validation and dissemination of agricultural technology have received much attention in recent times among researchers in Ghana. However, very limited information exists on the factors that influence willingness of farmers' participation. The present study identified the factors influencing willingness to participate in innovation platform and also tested the level of agreement among the identified constraints associated with participation using the Probit model and Kendall's coefficient of concordance respectively. Data for the study was collected from a cross sectional primary observations of 250 smallholder rice farmers in northern Ghana. The study observes, inter alia, that age of household head, household size and household income significantly influenced willingness to participate on the platform. The Kendall's coefficient of concordance value indicated that there was 21 percent agreement between the rankings of the participation constraints faced by the sampled rice farmers. Income-earning and younger household heads must be targeted coupled with situation of the platforms close to smallholder farmers to encourage participation.
Keywords: 330; Multi-stakeholder platform; Constraint; Probit; Kendalls coefficient of concordance; Northern Ghana